The effect of demographic factors on employees’ performance: A case of an owner-manager manufacturing firm - Godson Kwame Amegayibor (Annals of Human Resource Management Research, 2021)
Purpose: The goal of this study is to look into how demographic factors influence employee performance in an owner-manager manufacturing firm. Research Methodology: The research was carried out in an owner-manager firm in Cape Coast, Ghana's central region. For data translation and analysis, a quantitative approach and a correlational study design were used, as well as a census sampling technique to sample 400 employees, an interview schedule, multiple linear regression, and the Statistical Package for Social Sciences (SPSS) 20.0 Versions. Result: The findings show that age and education have an impact on employees’ performance. The findings also revealed that age and department have an impact on employee absenteeism. Again the result shows that age, education, and tenure respectively influences employees’ output. However, some demographic factors have no relationship with employees’ performance, absenteeism, or output. Limitation: Time constraints, assumptions about the underlying theory, and the unwillingness of respondents to give out information were all limitations. Contribution: SMEs owners and managers must not overlook these elements, as they have a variety of effects on employees’ performance, how they miss work, and output levels. It is thought that paying attention to an employee's age groups, level of education, the department they work in and what transpired there, and years of experience will go a long way in assisting them in performing to a satisfactory level and increasing their performance.